Physical activity in schools: it’s not just for the gym and recess. Introducing physical activity into the academic classroom to improve student engagement and performance - Ellner, Mark Robert (Kansas State University, 2019)
The time that students are asked to sit in classrooms each day can exceed eight hours. With a higher emphasis on academic outcomes, due to legislation such as No Child Left Behind and Common Core, both of which put a high priority on the results of standardized tests, curricula not deemed traditionally academic such as art and physical education are often pushed to the side (Stevens-Smith, 2016; Donnelly & Lambourne, 2011). While little evidence suggests that increased academic time leads to improved test scores, what is known is that increased academic time leads to less physical activity during a student’s education experience (Pangrazi, Beighle &Pangrazi, 2009; Blakemore, 2003). Current research suggests that there are multiple positive results that can be attributed to physical activity being incorporated into a student’s academic experience. Hanaford (2005), found through brain scans that children learn best when active because of the neurons that facilitate learning and retention being stimulated. Stevens-Smith (2016) stated, “While children are physically moving, they are developing neurological foundations that assist with problem solving, language development, and creativity” (p. 723). This study looks to explore how physical activity within the classroom academic setting impacts student engagement. Through classroom observations and focus group interviews with upper elementary teachers from a midwestern elementary school, the results of this study will provide how students react to specific types of physical activities in terms of curriculum engagement, classroom behavior, and academic performance. The use of grounded theory as a theoretical framework will allow for this study to develop new theory to learn what and how physical activities used are the most effective at increasing student engagement. Through the extensive coding and analysis, 13 concepts were developed and further analyzed to create four main categories. Those categories led to the main storyline of this study. While the original focus of this study was to look at specific physical activities present in the classrooms, what was found was that a broader and more natural approach to introducing physical activity into the academic learning environment was most effective for the teachers in this study. This study revealed that through the use of a constant natural freedom of movement theory, teachers are able to effectively enhance student engagement through the use of physical activity as a teaching strategy within the academic learning environment. The study also presented that while a number of barriers are prohibitive to using physical activity in the academic learning environment, the teachers have an overwhelmingly positive perception of physical activity as a student engagement strategy. The teachers believe that the incorporation of physical activity into the classroom allows for individual learning opportunities and increased student engagement, which ultimately leads to a love of learning.
Keywords: Physical activity; Engagement; Kinesthetic learning; Alternative seating; Academic learning; Elementary